Usuwanie odpadów niebezpiecznych jako zadanie gminy - Ostrowski, Adam (PRAWO i WIĘŹ, 2026)
For the purposes of this argument, the author analysed the legal provisions on the basis of which local governments perform waste management tasks, with particular emphasis on waste classified as hazardous. The shortcomings of the statutory regulations in this area were demonstrated. The author referred to case law in which local governments raised the issue of the nature of interpretation of the provisions defining the concept of municipal waste in practice. Proposals were presented on how to increase the efficiency of waste management in local government units. The paper concludes with proposals for legislative changes aimed at supporting local governments by introducing a provision into the Waste Act, stipulating that the tasks of the head of the local authority (mayor, city president), which, in the field of waste disposal, do not constitute municipal waste, are tasks within the scope of government administration, which, in accordance with the applicable regulations, are then financed from the state budget.